2017
DOI: 10.1038/s41598-017-09031-5
|View full text |Cite
|
Sign up to set email alerts
|

Designing of metallic nanocrystals embedded in non-stoichiometric perovskite nanomaterial and its surface-electronic characteristics

Abstract: Engineering of novel functional nanocomposite as like as the metallic nanocrystals supported non-stoichiometric perovskite nanomaterial in controlled parameters (size, shape and ratio of chemical characteristics) is a challengeable task. In this context, we present a facile route to fabricate and study its physicochemical property at real time mode in this report. Nanoscale pure Pb crystals surfaced on non-stoichiometric A-site deficient Pb1-xTiO3-y nanoparticle were fabricated when a precursor lead titanate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 61 publications
1
8
0
Order By: Relevance
“…Concerning the Ti 2 p XPS spectrum, the first component, around 458 eV, is attributed to the Ti 2 p 3/2 peak, whereas the second one around 463 eV is ascribed to the Ti 2 p 1/2 peak. The energy positions of both peaks coincide well with previous reports on different ferroelectric perovskites compounds 39,40 . The difference between Ti 2 p 3/2 and Ti 2 p 1/2 spin‐orbit splitting, which is around 5.5 eV, corresponds to Ti 4+ oxidation state.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Concerning the Ti 2 p XPS spectrum, the first component, around 458 eV, is attributed to the Ti 2 p 3/2 peak, whereas the second one around 463 eV is ascribed to the Ti 2 p 1/2 peak. The energy positions of both peaks coincide well with previous reports on different ferroelectric perovskites compounds 39,40 . The difference between Ti 2 p 3/2 and Ti 2 p 1/2 spin‐orbit splitting, which is around 5.5 eV, corresponds to Ti 4+ oxidation state.…”
Section: Resultssupporting
confidence: 89%
“…These peak positions correspond to Pb 2+ presents in the material lattice. 40 It is seen in Figure S3a,b that the binding energies of La 3d 5/2 are between 834.2 and 837.9 eV, confirming the existence of only La 3+ ions. 41 The energy difference between these peaks is about 4 eV, also in good agreement with the literature.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…The ferroelectrics, PT and PZT, were selected owing to their large and stable ferroelectric polarization, and they have been investigated in several prior studies that demonstrated a strong polarization-dependent modulation of the Schottky barrier height with the surface Au nanoparticles. For example, the ferroelectric PT has been characterized as an n -type semiconductor with a bandgap of ~2.7 eV (Reddy and Parida, 2013) and an electron affinity χ of ~3.5 eV (Pintilie et al, 2008; Li et al, 2012; Suriyaprakash et al, 2017). When Au (work function Φ M = 5.1 eV) is in contact with a normal semiconductor with a similar electron affinity as that of PT, the semiconductor bands bend upward at their surface, leading to a low-energy Schottky barrier on the order of ~0.1–0.3 eV (Zhang and Yates, 2012; Pintilie et al, 2014).…”
Section: Experimental Investigations Of Schottky Barrier Heights and mentioning
confidence: 99%